Design and development of multifunctional polyphosphoester-based nanoparticles for ultrahigh paclitaxel dual loading. Issue 41 (16th October 2017) - Zhang, Fuwu; Khan, Sarosh; Li, Richen; Smolen, Justin A.; Zhang, Shiyi; Zhu, Guizhi; Su, Lu; Jahnke, Ashlee A.; Elsabahy, Mahmoud; Chen, Xiaoyuan; Wooley, Karen L.
Abstract : Polyphosphoester-based nanoparticles are capable of loading paclitaxel chemically and physically, achieving ultrahigh equivalent paclitaxel aqueous concentrations. Abstract : Multifunctional polyphosphoester-based nanoparticles capable of loading paclitaxel (PTX) both chemically and physically were prepared, achieving an ultrahigh equivalent PTX aqueous concentration of 25.30 mg mL −1 . The dual-loaded nanoparticles were effective in killing cancer cells, which has the potential to minimize the amount of nanocarriers needed for clinical applications, due to their ultrahigh loading capacity.